Development of Aptamer-Based Nanomaterials for Biological Analysis - Pu, Y.; Liu, H.; Liu, B.; Liao, J.; Liu, J.; Zhao, Z.; Tan, W. (Current Molecular Medicine, 2013)
Aptamers selected from a large random sequence pool are oligonucleic acid or peptide molecules that bind to a specific target molecule with high affinity and sensitivity. Targets range from small molecules to proteins and peptides, even tissue or cells. As such, aptamers have captured the attention of scientists actively developing technologies for diverse biomedical applications. Particularly, when functionalized with nanomaterials, aptamers offer properties for both biomedical and bioanalytical applications. In this review, these features and properties are discussed with particular emphasis on the use of aptamer-based biosensor/detection platforms.
Keywords: cancer cells